Radiation-induced DNA Double Strand Breaks and Their Modulations by Treatments with Moringa oleifera Lam. Leaf Extracts: A Cancer Cell Culture Model - K. Boonsirichai; S. Jetawattana (PPIKSN-BATAN, 2014)
Gamma radiation brings deleterious effects upon human cells by inducing oxidative stress and DNA damages. Antioxidants have been shown to confer protective effects on irradiated normal cells. Moringa oleifera Lam. is a widely used nutritional supplement with antioxidant activities. This report showed that antioxidant-containing supplements, in addition to protecting normal cells, could protect cancer cells against genotoxic effects of gamma radiation. γ-H2AX immunofluorescent foci were utilized as an indicator of radiation-induced DNA double strand breaks. MCF-7 human breast adenocarcinoma cells were irradiated with 2-8 Gy gamma radiation. A linear relationship between the formation of γ-H2AX foci and radiation dose was observed with an average of 10 foci per cell per Gy. A 30-minute pretreatment of the cells with either the aqueous or the ethanolic extract of M. oleifera leaves could partially protect the cells from radiation-induced DNA double strand breaks. A pretreatment with 500 µg/mL aqueous extract reduced the number of foci formed by 15% when assayed at 30 minutes post-irradiation. The ethanolic extract was more effective; 500 µg/mL of its concentration reduced the number of foci among irradiated cells by 30%. The results indicated that irradiated cancer cells responded similarly to nutritional supplements containing antioxidants as irradiated normal cells. These natural antioxidants could confer protective effects upon cancer cells against gamma radiation.Received: 08 November 2013; Revised: 01 March 2014; Accepted: 17 March 2014